The Role of Slit-2 in Gestational Diabetes Mellitus and Its Effect on Pregnancy Outcome - Wang, Yan; Zhao, Shihua; Peng, Wei; Chen, Ying; Chi, Jingwei; Che, Kui; Wang, Yangang (Frontiers in Endocrinology, 2022)
Background Slit guidance ligand 2 (Slit2), as a member of the Slit family, can regulate the inflammatory response and glucose metabolism. The purpose of this study was to explore the expression of Slit2 in maternal and cord blood of gestational diabetes mellitus (GDM) patients and its potential importance in disease progression. Methods This study included 57 healthy pregnant women and 61 GDM patients. The levels of Slit2, C-reactive protein (CRP), monocyte chemoattractant protein-1 (MCP-1), C-peptide (C-P), fasting blood glucose (FBG) and fasting insulin (FINS) in maternal and cord blood were detected by ELISA. Results Slit2 levels in maternal and cord blood of the GDM patients were higher than those of the healthy controls. Slit2 levels in maternal and cord blood of the GDM patients were positively correlated with CRP and MCP-1 levels. The level of Slit2 in the maternal blood of the GDM patients was positively correlated with the level of Homeostasis model assessment insulin resistance (HOMA-IR) in maternal blood, and was negatively correlated with the level of Homeostasis model assessment –β (HOMA-β). We also found that the Slit2 level in the maternal blood of the GDM patients was negatively correlated with neonatal blood glucose and positively correlated with neonatal weight. Conclusion Our study suggests that the abnormal increase in Slit2 in GDM may be related to the pathogenesis of GDM, and it was correlated with neonatal blood glucose and weight in patients with GDM，suggesting that Slit2 may be a potential biomarker of GDM.